Inkjet‐Printing: A New Fabrication Technology for Organic Transistors. Issue 10 (12th September 2017) - Mattana, Giorgio; Loi, Alberto; Woytasik, Marion; Barbaro, Massimo; Noël, Vincent; Piro, Benoît
Abstract: Inkjet‐printing is one of the most important fabrication techniques in the field of printed electronics. Its main advantages include the possibility of fabricating, at ambient conditions and by employing a digital layout, a large variety of electronic devices on different types of substrates, including flexible plastic ones. In this paper, the utilization of inkjet‐printing as an important fabrication tool for the realization of organic transistors and circuits/sensing systems based on such type of transistors is reviewed. The most important aspects of the fabrication process, including ink formulation, printing deposition, and postprinting treatment, are described in detail. The most significant examples of inkjet‐printed organic transistors of different types (field‐effect, electrolyte‐gated, and electrochemical) are presented and finally an overview of their applications as building blocks of more complex electronic circuits and systems for the detection and quantification of specific measurands is provided. Abstract : The application of inkjet‐printing for the fabrication of organic thin film transistors (OTFTs) and OTFTs‐based circuits and sensing systems is reviewed in detail. Different aspects of the inkjet‐printing fabrication procedure (inks composition and rheological properties, postdeposition treatments, and OTFTs realization) are described and the most important results obtained in terms of single device and more complex circuits are summarized.